Formulation of Group Dynamics Effectiveness Index and Steps to Mobilise Users Group for Participatory Water Management (Indian Journal of Extension Education, 2011)
A tool Group Dynamics Effectiveness Index (GDEI) was formulated to measure group effectiveness of selected groups identifying different dimensions and their relative importance in it. The development of GDEI initiated with item analysis and indexing the items with respect to respective weightage delineated through scale product method. The GDEI included ten items viz. participation, decision making procedures, operation, maintenance & management functions, interpersonal trust, fund generation, social support, group atmosphere, membership feelings, group norms and empathy, which receive different weights for calculation of overall group dynamic effectiveness. Strategy for mobilization of effective user group for participatory irrigation management was developed for three distinct phases viz. group formation (0-3 months), group stabilization (4-15 months) and self-helping phase (16-36 months) in which Eight main steps and fourty five sub-steps were conceptualized.